Structural mechanism for versatile cargo recognition by the yeast class V myosin Myo2 - Tang, Kun (J Biol Chem, 2019)
Class V myosins are actin-dependent motors, which recognize numerous cellular cargos mainly via the C-terminal globular tail domain (GTD). Myo2, a yeast class V myosin, can transport a broad range of organelles. However, little is known about the capacity of Myo2-GTD to recognize such a diverse array of cargos specifically at the molecular level. Here, we solved crystal structures of Myo2-GTD (at 1.9–3.1 Å resolutions) in complex with three cargo adaptor proteins: Smy1 (for polarization of secretory vesicles), Inp2 (for peroxisome transport), and Mmr1 (for mitochondria transport). The structures of Smy1- and Inp2-bound Myo2-GTD, along with site-directed mutagenesis experiments, revealed a binding site in subdomain-I having a hydrophobic groove with high flexibility enabling Myo2-GTD to accommodate different protein sequences. The Myo2-GTD-Mmr1 complex structure confirmed and complemented a previously identified mitochondrion/vacuole-specific binding region. Moreover, differences between the conformations and locations of cargo-binding sites identified here for Myo2 and those reported for mammalian MyoVA (MyoVA) suggest that class V myosins potentially have co-evolved with their specific cargos. Our structural and biochemical analysis not only uncovers a molecular mechanism that explains the diverse cargo recognition by Myo2-GTD, but also provides structural information useful for future functional studies of class V myosins in cargo transport.